The status and characteristics of university-industry collaboration in a research university - Abu Mansor, Nur Naha (Penerbit UTM Press, 2015)
The increasing reliance on knowledge in industry and services is generating strong incentives to develop more efficient ways to transfer the discoveries made in academia to business. This paper mainly focuses to identify the status and characteristics of university-industry (UI) collaborations at a research university. Moreover a quantitative research method was adopted in this study. The sample was selected from Universiti Teknologi Malaysia (UTM). A total of 42 UTM centers participated in this survey. The findings demonstrate the type of existing UI collaborations and mobility at UTM. Furthermore, the result indicated the characteristics of university partners.